2020
DOI: 10.4049/jimmunol.1801629
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 Receptor Expression on Activated Human Th Cells Is Regulated by IL-4, and IL-3 Synergizes with IL-4 to Enhance Th2 Cell Differentiation

Abstract: IL-3, a cytokine secreted by activated T lymphocytes, is known to regulate the proliferation, survival, and differentiation of hematopoietic cells. However, the role of IL-3 in regulation of T cell functions is not fully delineated. Previously, we have reported that IL-3 plays an important role in development of regulatory T cells in mice. In this study, we investigated the regulation of IL-3R expression on human Th cells and also examined the role of IL-3 in effector functions of these cells. We found that hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The Th1 and Th2 subgroups of mice can secrete IL-2 and IL-4, respectively, and both IL-2 and IL-4 can promote the proliferation of T cells [43,44]. In addition, IL-4 can also promote the expression of B cells, enhance the antigen presentation ability of B cells, increase IgG1 and IgE levels, and make the responses of immune system to antigen stimulation [45,46]. Gong et al found that Bletilla baicalensis polysaccharides could significantly enhance the levels of IL-2 and IL-4 in immunosuppressed mice [47] which is similar with the effect of DZMP in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The Th1 and Th2 subgroups of mice can secrete IL-2 and IL-4, respectively, and both IL-2 and IL-4 can promote the proliferation of T cells [43,44]. In addition, IL-4 can also promote the expression of B cells, enhance the antigen presentation ability of B cells, increase IgG1 and IgE levels, and make the responses of immune system to antigen stimulation [45,46]. Gong et al found that Bletilla baicalensis polysaccharides could significantly enhance the levels of IL-2 and IL-4 in immunosuppressed mice [47] which is similar with the effect of DZMP in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play a very important role in infection, inflammation, and cancer ( Fu et al., 2018 ; Fan et al., 2019 ; Guo et al., 2019 ; Meng et al., 2019 ). Increased level of IL-3, IL-5, IL-1β, GM-CSF could help active the lymphocytes and promote lymphocytes proliferation( Kumar et al., 2020 ). IL-3, IL-5, and GM-CSF are produced primarily by activated T cells, promote myeloid cell proliferation and differentiation, and play a role in a variety of human diseases, particularly cancer and inflammation( Koh et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FOSL1 and FOSL2 negatively-regulated Th1-lineage genes (TBX21 109,110 , IFNG 111 , IL12RB2 112 and HOPX 113 ), while promoting the expression of Th2-specific factors (GATA3 114 , IL13 115 and IL3 116 ). It however remains to be understood if these AP-1 factors restrain Th17 responses by modulating helper-T-cell diversification.…”
Section: Discussionmentioning
confidence: 99%